Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1158/1078-0432.ccr-07-1328
|View full text |Cite
|
Sign up to set email alerts
|

Activation of KIF4A as a Prognostic Biomarker and Therapeutic Target for Lung Cancer

Abstract: Purpose and Experimental Design: To identify molecules that might be useful as diagnostic/ prognostic biomarkers and as targets for the development of new molecular therapies, we screened genes that were highly transactivated in a large proportion of 101lung cancers by means of a cDNA microarray representing 27,648 genes. We found a gene encoding KIF4A, a kinesin family member 4A, as one of such candidates. Tumor tissue microarray was applied to examine the expression of KIF4A protein and its clinicopathologic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
116
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(128 citation statements)
references
References 46 publications
12
116
0
Order By: Relevance
“…In agreement with the clinical experience, we noted that cell-cycle mRNAs followed a gradient ranging from a few fold to more than 50-fold up-regulation, which may limit the isolated use of this parameter for diagnostic purposes. A number of the up-regulated transcripts including anillin , ARP 2/3 complex (Otsubo et al 2004), abnormal spindle homolog (Ayllon & O'connor 2007, Lin et al 2008, centromere protein F (Campone et al 2008), KIF4A (Taniwaki et al 2007), maternal embryonic leucine zipper kinase (Gray et al 2005), NIMA-related kinase 2 (Hayward & Fry 2006), PDZ-binding kinase, protein regulator of cytokinesis 1 (Boukarabila et al 2009), regulator of chromosome condensation 2 (Stacey et al 2008), encoded proteins that are directly involved in mitosis and several of them are over-expressed in other cancers. In particular, transcripts encoding ribonucleotide reductase small subunit, RRM2, and topoisomerase 2a, TOP2A respectively, are intimately connected to cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with the clinical experience, we noted that cell-cycle mRNAs followed a gradient ranging from a few fold to more than 50-fold up-regulation, which may limit the isolated use of this parameter for diagnostic purposes. A number of the up-regulated transcripts including anillin , ARP 2/3 complex (Otsubo et al 2004), abnormal spindle homolog (Ayllon & O'connor 2007, Lin et al 2008, centromere protein F (Campone et al 2008), KIF4A (Taniwaki et al 2007), maternal embryonic leucine zipper kinase (Gray et al 2005), NIMA-related kinase 2 (Hayward & Fry 2006), PDZ-binding kinase, protein regulator of cytokinesis 1 (Boukarabila et al 2009), regulator of chromosome condensation 2 (Stacey et al 2008), encoded proteins that are directly involved in mitosis and several of them are over-expressed in other cancers. In particular, transcripts encoding ribonucleotide reductase small subunit, RRM2, and topoisomerase 2a, TOP2A respectively, are intimately connected to cancer.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Narayan et al 49 reported that the expression of KIF4A mRNA in cervical cancer was much higher than that in normal tissues. Taniwaki et al 18 demonstrated that the KIF4A gene was activated in nonsmall cell lung cancer (NSCLC) cells and that treatment of NSCLC cells with specific siRNA to knockdown KIF4A expression resulted in the suppression of cancer cell growth. Moreover, patients with NSCLC who had KIF4A-positive tumors had a shorter cancer-free survival than patients who had KIF4A-negative tumors.…”
Section: Kinesin-4 Familymentioning
confidence: 99%
“…Alteration of their expression and functions leads to human disease, including cancer development and progression. For example, alterations of KIF3, 13 KIF1B, 14 KIF14, 15 and Kid 16 proteins were observed in breast cancer; KIF14 17 and KIF4A 18 were altered in lung cancer; and KIF1B was down-regulated in neurofibroma. 19 In addition, altered expression of EG5, 20 CENP-E, 21 KIF5B, 22 and KIF18A 23 proteins was associated with the development of different human cancers.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…KIF4A has been reported to participate in a variety of cell processes, including intracellular trafficking of HIV gag and integrin-β 1 (Martinez et al, 2008;Willemsen et al, 2014), mitotic progression (Zhu and Jiang, 2005;Wandke et al, 2012), DNA damage response (Wu et al, 2008) and brain neuron development (Midorikawa et al, 2006). It has been also reported that KIF4A was upregulated in lung cancer and could serve as a prognostic biomarker and therapeutic target for lung cancer (Taniwaki et al, 2007;Zhu et al, 2015). Our previous studies showed that KIF4A is also involved in cisplatin resistance in lung cancer cells (Xiao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%